With Darkness Came Stars A Memoir - Flack, Audrey 1931-2024 (Penn State University Press, 2024)
Only in the darkest moments of our lives do the brightest stars appear.An artist, mother, teacher, and rebel, Audrey Flack is counted among the most important American artists of the twentieth century. In With Darkness Came Stars, she recounts and reflects upon a life fully lived. Flack came up in the New York art scene when the city was fast becoming a world arts center. She had a studio in the Bowery and frequented the Cedar Tavern, where she rubbed elbows with Jackson Pollock, Willem and Elaine de Kooning, Grace Hartigan, and other giants of the Abstract Expressionist movement. After leaving that scene and starting a family, she spearheaded Photorealist painting, alongside the likes of Chuck Close and Richard Estes. Flack has lived a remarkable life, successfully navigating a vibrant and virulently sexist art world, escaping an abusive marriage, and reshaping the rules of art creation in the middle of the twentieth century-all while raising two children, one with severe autism. Her story is full of strife and striving, but as an artist, Flack has always been able to find the beauty in it